THE ADDITIONAL KINESIOTAPING ON ABDOMINAL INTERVENTION STRETCHING EXERCISE IS BETTER THAN ABDOMINAL STRETCHING EXERCISE INTERVENTION AGAINST FUCTIONAL LIMITATION RESULT PAIN PRIMARY DYSMENORRHEA IN FEMALE ADOLESCENT STUDENT SMP NEGERI 9 DENPASAR - Agusti, Ni Nyoman Satria Mas; Winaya, I Made Niko; Adiputra, Luh Made Indah Sri Handari (Majalah Ilmiah Fisioterapi Indonesia; Vol 6 No 1 (2018): Majalah Ilmiah Fisioterapi IndonesiaDO - 10.24843/MIFI.2018.v06.i01.p12, 2018)
ABSTRACT This study was conducted to analyze the addition of kinesiotaping in the abdominal intervention stretching exercise better than the intervention of abdominal stretching exercise in primary dysmenorrhea. This study was an experimental pre-test and post-test control group design, each group consisting of 11 people, with kinesiotaping on abdominal stretching exercise intervention in Group 1 and giving abdominal stretching exercise intervention in Group 2 as a control group. Measurement of pain reduction rate was performed using Menstrual Distress Questionnaire (MDQ). After obtaining the data, the results showed that the addition of kinesiotaping to the abdominal intervention stretching exercise had a decrease in pain of 42.55 ± 4.25 whereas only with abdominal exercise stretching exercise had decreased pain of 23.45 ± 3.45 with p = 0.000 (p <0.05). Keywords: Primary dysmenorrhea, abdominal stretching exercise, kinesiotaping, Menstrual Distress Questionnaire (MDQ)